MISCONCEPTION ANALYSIS OF THE STRUCTURE AND FUNCTION OF LIVING THINGS WITH THE CRI METHOD - Meiga Husnul Kholifah; Mega Novita; Sumarno Sumarno; Harto Nuroso; Siti Patonah (Universitas Negeri Makassar, 2024)
This study aims to analyze students' misconceptions about the material of the structure and function of living things using the CRI method. This research is expected to provide useful information to improve the quality of science learning and help students to understand the concept of the structure and function of living things better. This study used a descriptive research design with a quantitative approach with 20 multiple choice questions to analyze student misconceptions about the structure and function of living things using the Certainty of Response Index (CRI) method. The CRI scale used consists of four options, namely very unsure, unsure, sure, and very sure. This research was conducted at SMP N 2 Karangawen on students of class VIII D totaling 26 students who had studied the material of the structure and function of living things. Based on the results of the study, the data obtained that the percentage of students' misconceptions is an average percentage of 63.27%.